Pengaruh tingkat likuiditas, Islamic corporate governance dan efisiensi operasional terhadap kinerja keuangan dengan risiko pembiayaan sebagai variabel moderating - Yastutik, Indri; Yudiana, Fetria Eka (Nur Science Institute, 2021)
This study aims to determine the effect of liquidity level, Islamic corporate governance (ICG), and operational efficiency on financial performance with financing risk as a moderating variable. The type of research used is quantitative, and the type of data used is secondary data with the population used is Islamic Commercial Banks that meet the criteria. The sampling technique in this study used a purposive sampling technique. So the sample used as the object of research is 11 Islamic Sharia Commercial Banks in Indonesia for the 2015-2019 period. The data analysis technique used is the MRA test. The results of this study indicate that the FDR, ICG, and NPF variables have a significant adverse effect on ROA, while BOPO has a significant positive effect on ROA. Moreover, the NPF variable can moderate the effect of FDR and BOPO on ROA, while the NPF variable cannot moderate the effect of ICG on ROA.